Effects of volatile anesthetics on store-operated Ca2+ influx in airway smooth muscle - (:unkn) unknown (My University, 2004)
Background: In airway smooth muscle (ASM), volatile anesthetics deplete sarcoplasmic reticulum (SR) Ca2+ stores by increasing Ca2+ "leak." Accordingly, SR replenishment becomes dependent on Ca 2+ influx. Depletion of SR Ca2+ stores triggers Ca 2+ influx via specific plasma membrane channels, store-operated Ca2+ channels (SOCC). We hypothesized that anesthetics inhibit SOCC triggered by increased SR Ca2+ "leak," preventing SR replenishment and enhancing ASM relaxation. Methods: In porcine ASM cells, SR Ca2+ was depleted by cyclopiazonic acid or caffeine in 0 extracellular Ca2+, nifedipine and KCl (preventing Ca2+ influx through L-type and SOCC channels). Extracellular Ca2+ was rapidly introduced to selectively activate SOCC. After SOCC activation, SR was replenished and the protocol repeated in the presence of 1 or 2 minimum alveolar concentration halothane, isoflurane, or sevoflurane. In other cells, characteristics of SOCC and interactions between acetylcholine (Ach) and volatile anesthetics were examined. Results: Cyclopiazonic acid produced slow SR leak, whereas the caffeine response was transient in ASM cells. Reintroduction of extracellular Ca2+ rapidly increased [Ca2+] i. This influx was insensitive to nifedipine, SKF-96365, and KBR-7943, inhibited by Ni2+ and blockade of inositol 1,4,5-triphosphate-induced SR Ca2+ release, and enhanced by ACh. Preexposure to 1 or 2 minimum alveolar concentration halothane completely inhibited Ca2+ influx when extracellular Ca2+ was reintroduced, whereas isoflurane and sevoflurane produced less inhibition. Only halothane and isoflurane inhibited ACh-induced augmentation of Ca2+ influx. Conclusion: Volatile anesthetics inhibit a Ni2+/La 3+-sensitive store-operated Ca2+ influx mechanism in porcine ASM cells, which likely helps maintain anesthetic-induced bronchodilation.